ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN DU PONT SYSTEM PADA PT SUMBER ALFARIA TRIJAYA Tbk PERIODE 2015-2017 - Liliana Sonya Loppies; Dicky Sagitaputra (Soso-Q : Jurnal Manajemen, 2020)
The retail business in Indonesia is increasingly growing and business competition shows a fairly rapid development, but it is not an obstacle for retail entrepreneurs to increase the number of outlets in various regions, PT Sumber Alfaria Trijaya which is the object of research at this writing is engaged in the retail distribution of products consumer. This study aims to analyze performance by using the Du Pont system which is a comprehensive measurement tool covering company operations through owned resources to produce net profits that combine debt, asset turnover and profit margins that interact to determine the profitability of assets owned by the company and the return on equity (ROE) generated. From the results of data analysis obtained that the level of Net Profit Margin during the last three years by PT Sumber Alfaria Trijaya Tbk has increased in 2016, amounting to 0.99% (up 0.03%) from 0.96% in 2015 The results of the calculation of Total Asset Turnover over the last three years by PT Sumber Alfaria Trijaya Tbk from 2015 to 2017 decreased in 2016, amounting to 2.88 times (down 0.3 times) from 3.18 times in 2015. Results the calculation of Return on Investment for the last three years by PT Sumber Alfaria Trijaya Tbk from 2015 to 2017 has decreased. ROI in 2016 decreased by 2.85% (down 0.2%) from 3.05% in 2015. The results of the calculation of Equity Multipier over the last three years by PT Sumber Alfaria Trijaya Tbk have increased in 2016 and in 2017 decreased The results of the calculation of Return on Equity over the past three years by PT Sumber Alfaria Trijaya Tbk experienced an increase in 2016 of 10.49% (up 0.94%) from 9.55% in 2015. The financial performance of PT. Sumber Alfaria Trijaya, Tbk, which was analyzed using the Du Pont System Tbk method during the 2015 period was not good Keywords: du pont system, financial performance